2016
DOI: 10.1002/ardp.201600066
|View full text |Cite
|
Sign up to set email alerts
|

Fragment Discovery for the Design of Nitrogen Heterocycles as Mycobacterium tuberculosis Dihydrofolate Reductase Inhibitors

Abstract: Fragment-based drug design was used to identify Mycobacterium tuberculosis (Mtb) dihydrofolate reductase (DHFR) inhibitors. Screening of ligands against the Mtb DHFR enzyme resulted in the identification of multiple fragment hits with IC50 values in the range of 38-90 μM versus Mtb DHFR and minimum inhibitory concentration (MIC) values in the range of 31.5-125 μg/mL. These fragment scaffolds would be useful for anti-tubercular drug design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In the context of antifolate resistance, development of new generation antifolates based on novel chemotypes is warranted. Although the fragment-based screening approach has been successfully applied to DHFR enzymes in various bacteria and protozoa 41,42 , no similar study has yet been reported in the malaria parasite Plasmodium falciparum. Here, we describe the first fragment-based screening on PfDHFR.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of antifolate resistance, development of new generation antifolates based on novel chemotypes is warranted. Although the fragment-based screening approach has been successfully applied to DHFR enzymes in various bacteria and protozoa 41,42 , no similar study has yet been reported in the malaria parasite Plasmodium falciparum. Here, we describe the first fragment-based screening on PfDHFR.…”
Section: Discussionmentioning
confidence: 99%
“…These fragments showed high glide score from À 6.10 to À 7.85 kcal/mol. [45] Compound 134 exhibited remarkably anti-tubercular activity with MIC value of 6.25 μg/mL as compared to standard drug Rifampicin (0.313 μg/mL). The molecular docking study revealed that compound 134 showed good interaction with amino acid residues of glycerol (GOL) binding site of Mtb-DHFR enzyme such as Ile20, Arg23, Phe31, Leu50, Pro51 and Val54 among these residue Phe31 and Arg23 showed hydrogen bonding interaction.…”
Section: Antitubercular Activitymentioning
confidence: 95%
“…1), belonging to the xanthine compounds, can decrease smooth muscle tension, open air passages and promote the release of endogenous epinephrine and norepinephrine [1] . Theophylline can also inhibit the release of calcium ions (Ca 2+ ) from the endoplasmic reticulum of smooth muscle cells and reduce the intracellular Ca 2+ concentration, thereby generating an airway dilating effect, and it is a potent smooth muscle relaxant [2] . Theophylline is used to treat diseases including bronchial asthma, acute bronchitis, asthmatic bronchitis, and obstructive emphysema, in order to relieve the symptoms of wheezing [3,4] .…”
Section: Introductionmentioning
confidence: 99%